Cognitive Level through Creativity, Strategy and Belief in Problem Solving for Engineering Students - Omar, Norasyikin; Mohamad, Mimi Mohaffyza; Paimin, Aini Nazura (Online Journal for TVET Practitioners, 2020)
Cognitive is an important aspect of a student’s success. Students with good cognitive levels have the potential to excel in academic achievement. This study involved the level of mastery of the cognitive elements of creativity, strategy and belief among engineering students at Universiti Tun Hussein Onn Malaysia (UTHM). In the context of this study, creative elements refer to the application of thinking by engineering students based on discovery, understanding, analysis and applying knowledge in new situations to solve problems. Strategic elements refer to the problem-solving process that involves several phases: engaging, resolving problems, exploring, planning, executing and reviewing. While the belief element refers to the confidence that is embodied in the belief in the ability to solve the problem. The research method used was a quantitative approach through questionnaire to 200 respondents of engineering students at UTHM. For the determination of gender frequency, the degree of mastery of the cognitive elements obtained, was analyzed using descriptive statistics. As for inference statistics, the MANOVA test was used to detect differences in mastery of cognitive elements in engineering students. The findings indicate that the number of male students who choose engineering is higher than female students and the level of mastery of creative elements is higher in solving engineering learning problems at UTHM. There is a significant difference between mastery of the cognitive element in engineering students. In conclusion, there is a need to improve the level of mastery of strategy and belief elements to help engineering students excellent.